School indoor air quality and health risk on the junior high schools students in Depok, Indonesia - Pakpahan, Sasnila; Wispriyono, Bambang; Hartono, Budi; Jalaludin, Juliana (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: School environment represents an important microenvironment for students who spend 6-8 hours in classrooms. Indoor air quality is linked to several respiratory diseases in the school age group. This research aims to study indoor air quality of schools at different environmental characteristic and assess its health risks to students. Methods: This research measured air quality (PM2.5, PM10, CO2, and HCHO) in three junior high schools and followed by health risk assessment. Results: This research found that the mean or median level of indoor PM2.5 and PM10 in all three schools exceeded the standard value with health risks (HQ> 1) for PM2.5 in all three schools and PM10 in two schools. Whereas carbon dioxide and formaldehyde concentrations were still safe and did not inflict health risks (HQ < 1). The scenario for managing the health risk of PM2.5 and PM10 exposure was to control the exposure at a safe threshold of PM2.5 0.035 mg/m3; 0.043 mg/m3 and PM10 0.144 mg/m3 for most of the population at normal school time. Conclusion: It was concluded that the level of indoor particulate matters indicates poor indoor air quality in all three schools at different environmental characteristic and inflicts health risk on students so that the health risk management is required.